ARCHITECTURAL EDUCATION AS A NEW STAGE OF DEVELOPMENT: Array - Popova, O.; Malik, N. (Municipal economy of cities. Series: «Economy science», 2020)
The article considers the peculiarities of improvement and principles of the strategy of architectural education and the training peculiarities of modern specialists-architects for a new social order to improve the quality of professional activity. The need to improve the quality of architectural education and training of specialists is described. Implementation of programs of environmental ecological protection, rational using of natural resources, formation of a full-fledged human living environment by means of garden and park architecture, preservation of the natural environment in the city and creation of anthropogenic landscapes is a professional task of architects. New forms of creative activity are ahead of the theory and methodology of architectural design, which include everything new in technical and cultural progress. Digital technologies have penetrated into all spheres of human activity and today it is impossible to imagine modern architecture without their use. The introduction of digital technologies in the educational process in higher education in the training of future architects has become a matter of time. Computer and information technology are only a tool, but not a universal tool that can replace all areas of educational activity in the field of higher architectural education. The potential and creative capabilities of modern information technology in the training of future architects is not fully used, which shifts the emphasis of vocational education towards technocratization to the detriment of the creative, artistic component. Architecture is both art, and engineering, and construction. Digital systems are no longer only amplifiers of the speed of human action, not only new means of analysis, formation and perception, but also integral components of design, which is understood as creative activity. A special place in the training of an architect is occupied by creative design. Science and the broad humanity education are becoming a breeding ground for architectural creativity. This determines the tasks of training and education of the architect. The organization of architectural education as a holistic system of architect’s activities must take into account the fundamental changes that under the influence of social development and scientific and technical, economic and social forecasts occur in the activities of the architect. Ideological and social views of the architect, his spatial, constructive and aesthetic ideas are expressed in the artistic form and stylistic nature of the architectural work. Architectural and artistic image of architecture is invariably formed from the worldview; current issues of the time, from ideas about what should be an artificial space and what requirements it must meet.